Proyek Penguatan Profil Pelajar Pancasila Melalui Kegiatan Cooking di SMP Negeri 1 Medan (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study aims to describe the implementation of the Pancasila Student Profile Strengthening Project (P5) through Fun Cooking activities at SMP Negeri 1 Medan. This activity is part of the implementation of the Independent Curriculum with the theme "Sustainable Lifestyle" which aims to develop students' character values in accordance with the six dimensions of the Pancasila Student Profile, namely: faith and devotion to God Almighty and noble character, global diversity, mutual cooperation, independence, critical reasoning, and creativity. This study uses a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The research subjects consisted of facilitator teachers and seventh grade students who were directly involved in the project activities. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results showed that the Fun Cooking activity was implemented systematically through the stages of planning, implementation, reflection, and evaluation. This activity successfully fostered collaborative attitudes, creativity, responsibility, and students' awareness of a healthy and environmentally friendly lifestyle. Obstacles encountered, such as limited cooking utensils, differences in discipline levels, and time constraints, were overcome through various strategies such as scheduling, student coaching, and the use of personal utensils. In conclusion, the implementation of the P5 Project through the Fun Cooking activity at SMP Negeri 1 Medan was effective in shaping student character in accordance with the Pancasila Student Profile. This activity can serve as an example of good practice for other schools in implementing the Merdeka Curriculum in a contextual and enjoyable manner. Keywords: Strengthening Project, Pancasila Student Profile, Fun Cooking